Infections, resistance and antibiotic therapy in an internal medicine service - Pinto, Isabel C. (2014)
Currently, bacterial resistance to antibiotics is one of the greatest health challenges, particularly in Medicine Services. In this service you will find the largest number of patients with infectious disease, which is a major cause of hospitalization. It is intended to determine the rates of infectivity, the etiology of infections and patterns of antimicrobial susceptibility in the service of Medicine from Centro Hospitalar do Nordeste (CHNE)-Unidade Hospitalar de Bragança. During the period between January 1 and December 31 of year 2008 were received at the hospital laboratory 3547 bacteriological examination, of which 363 with positive results. In urine cultures identified an infectivity rate of 9.04%, noting that these 64.15% are due to E. Coli. As for the cultures of sputum, there was an infectivity rate of 19.68%, being that, of these 23.23% were Staphylococcus aureus. Blood cultures identified an infectivity rate of 5.66%, this should be mainly to the presence of Staphylococcus aureus (25.00%). Gram-negative (P.aeruginosa, E.coli e Klebsiella pneumoniae) showed the majority of resistance to Penicilins and Cefalosporins, belong to the group of b-lactam antibiotics. Staphylococcus aureus were resistant to Methicilin, one MRSA strain.